2019
DOI: 10.1177/0033354919874074
|View full text |Cite
|
Sign up to set email alerts
|

Online Health Information Seeking Among US Adults: Measuring Progress Toward a Healthy People 2020 Objective

Abstract: Objective: During the past decade, the availability of health information online has increased dramatically. We assessed progress toward the Healthy People 2020 (HP2020) health communication and health information technology objective of increasing the proportion of health information seekers who easily access health information online. Methods: We used data from 4 administrations of the Health Information National Trends Survey (HINTS 2008-2017) (N = 18 103). We conducted multivariable logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(158 citation statements)
references
References 31 publications
4
136
1
Order By: Relevance
“…Consistent with prior HINTS studies, primary predictors of interest were gender, race/ethnicity, age, education, income, home ownership, and nativity [ 28 , 32 ]. Consistent with prior HINTS analyses, missing responses were imputed using hot-deck imputation method to preserve the distribution of observed responses [ 34 ].…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Consistent with prior HINTS studies, primary predictors of interest were gender, race/ethnicity, age, education, income, home ownership, and nativity [ 28 , 32 ]. Consistent with prior HINTS analyses, missing responses were imputed using hot-deck imputation method to preserve the distribution of observed responses [ 34 ].…”
Section: Methodsmentioning
confidence: 93%
“…While many studies have examined use of the internet for health-related purposes for specific health conditions, gaps remain in examining disparities in use for a broad range of purposes including communication with healthcare professionals, health-related social media use, and general health information seeking [ 28 , 29 ]. Further, few studies have examined disparities in health-related internet use (HRIU) across a variety of demographic and health factors among a nationally representative dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Since the report on HRIU among cancer survivors by Chou and colleagues, the online landscape has considerably shifted, where 90% of Americans reported using the internet compared with the year 2000, when nearly half the American adult population did not use the internet, per a 2019 report from the Pew Research Center [17]. In the general US population, the use of the internet as the first source for health information has risen across the years [1,18]. Upon examining the individual types of HRIU in cancer survivors, Chou and colleagues found a significant trend across the years for all types of HRIU except cancer information seeking.…”
Section: Introductionmentioning
confidence: 99%
“…Even though health care professionals may not be discussing these endpoints with patients [4], previous research has found that patients with cancer actively seek information online [17]. However, many people are still frustrated by their online health searches [18]. In line with this finding, many of the definitions we identified used technical language that may not be easily understood.…”
Section: Discussionmentioning
confidence: 92%